2011
DOI: 10.1088/0004-637x/738/1/21
|View full text |Cite
|
Sign up to set email alerts
|

Helium Shell Detonations on Low-Mass White Dwarfs as a Possible Explanation for Sn 2005e

Abstract: Recently several type Ib supernovae (SNe; with the prototypical SN 2005E) have been shown to have atypical properties. These SNe are faint (absolute peak magnitude of ∼ −15) and fast SNe that show unique composition. They are inferred to have low ejecta mass (a few tenths of a solar mass) and to be highly enriched in calcium, but poor in silicon elements and nickel. These SNe were therefore suggested to belong to a new class of calcium-rich faint SNe explosions. Their properties were proposed to be the result … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
212
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(231 citation statements)
references
References 44 publications
18
212
1
Order By: Relevance
“…If the progenitor system is not a NS-WD binary but rather a WD-WD binary (e.g., Perets et al 2010;Waldman et al 2011;Sim et al 2012;Dessart & Hillier 2015), then the remote locations require a different origin than SN kicks. One possibility, as noted above, is that group and cluster environments have a large proportion of stars in ICL, resulting from galaxy-galaxy stripping and galaxy mergers in the formation of the cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the progenitor system is not a NS-WD binary but rather a WD-WD binary (e.g., Perets et al 2010;Waldman et al 2011;Sim et al 2012;Dessart & Hillier 2015), then the remote locations require a different origin than SN kicks. One possibility, as noted above, is that group and cluster environments have a large proportion of stars in ICL, resulting from galaxy-galaxy stripping and galaxy mergers in the formation of the cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Perets et al (2010) suggested SN 2005E may be the result of He detonation from accretion from a He white dwarf onto a CO white dwarf, one of several variants of WD-WD progenitors proposed (Waldman et al 2011;Sim et al 2012;Dessart & Hillier 2015). Another possibility is the tidal detonation of a He white dwarf by a neutron star or stellar-mass black hole (Metzger 2012;Sell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…References for individual Ca-rich gap transients are provided in the main text. SN 2005E could also be reproduced by a combination of mostly 48 Cr, 52 Fe and 44 Ti decay, in which case, however, a ridiculously high 44 Ti mass in excess of 1 M would be needed (Waldman et al, 2011;Kasliwal et al, 2012). Without a more precise knowledge of the ejecta mass, this degeneracy cannot be resolved easily.…”
Section: Light Curves and Peak Luminositymentioning
confidence: 99%
“…An acceptable match to the bolometric light curves of Ca-rich transients can probably be obtained if these parameters are chosen accordingly. For instance, Waldman et al (2011) found that the detonation of a 0.2 M He shell on top of a 0.45 M WD provides a good match to the bolometric peak of SN 2005E, but a somewhat too rapid decline. For the same initial conditions, Sim et al (2012) obtained a slightly more complete nucleosynthesis, favouring the production of the short-lived 48 Cr at the expense of 44 Ti, resulting in a significantly brighter light-curve peak.…”
Section: Explosion Modelsmentioning
confidence: 99%
“…The relatively large abundances of intermediate elements such as 44 Ti can provide a more unique signature for He-rich collisions, though high abundances of these components can also be produced in the SD sub-Chandrasekhar and .Ia explosion models (Woosley et al 1986;Livne & Glasner 1991;Bildsten et al 2007;Shen & Bildsten 2009;Perets et al 2010;Waldman et al 2011)). Interestingly, recent observations (Troja et al 2014) suggest that the 44 Ti abundances in Tycho SN remnant are comparable with the abundances we find in the Helium rich collisions (even those with low-mass He-layer).…”
Section: Comparison With Other Models Of Type Iamentioning
confidence: 99%